2005
DOI: 10.1159/000086369
|View full text |Cite
|
Sign up to set email alerts
|

Why Do Older People Report Fewer Headaches?

Abstract: Background: We have previously confirmed a clear decline in headache prevalence with increasing age. This parallels the pattern in other painful conditions but the age-related decline in prevalence is greater for headache. Objective: To investigate whether the decline in headache prevalence with age was associated with the elimination of work-related factors, increases in other health problems or concomitant use of pain-relieving medicines. We discuss these and other possible explanations from the literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…These figures are lower than studies of younger populations. However, this is not surprising because other studies have found that the prevalence of headache diminishes with age [8].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…These figures are lower than studies of younger populations. However, this is not surprising because other studies have found that the prevalence of headache diminishes with age [8].…”
Section: Discussionmentioning
confidence: 76%
“…Compared to younger populations, community-based epidemiological studies of older adults are rare. Most of these studies have been conducted outside of the United States [1][2][3][4][5][6][7][8][9][10][11]. Only two epidemiological studies of older adults have been conducted in the United States [12,13], one of which focused only on headache lasting at least 4 hours.…”
mentioning
confidence: 99%
“…Improvements in health and psychological well-being around retirement transition have previously been reported also in some other studies (39–44). However, earlier cross-sectional analyses have found no differences in headache prevalence between working and retired persons (45).…”
Section: Discussionmentioning
confidence: 88%
“…It seems that the occurrence of headaches in the elderly is underestimated [ 31 ]. In the British study, it was observed that the prevalence of headaches was at a similar level in people between 18 and 54 years of age, and decreased to 5% in the oldest age group aged 75–101 years [ 24 ].…”
Section: Discussionmentioning
confidence: 99%